Beckman Spacecraft Cabin Analyzer with open lid - Beckman Instruments Photographic Services Section (1967)
The Spacecraft Cabin Analyzer (SCA) was used in NASA's Apollo program, measuring oxygen pressure in the cabin as well as astronauts' spacesuits.
Keywords: Scientific apparatus and instruments; Oxygen--Measurement; Oxygen--Analysis; Beckman Instruments, Inc.